Search Review On Substance Abuse among Youth: A Harsh Reality on Drug Facts. (International Journal of Food and Nutritional Sciences, 2022)
Substance abuse is a public health problem globally. The prevalence of substance abuse among youth is alarming. The problem not only harms individuals but also negatively affects families and society.